Glucagon-like peptide-1 receptor agonist and sodium-glucose cotransporter 2 inhibitor use among adults with diabetes mellitus by cardiovascular-kidney disease risk: National Health and Nutrition Examination Surveys, 2015-2020 - Joshua A. Jacobs; Alexander R. Zheutlin; Catherine G. Derington; Jordan B. King; Ambarish Pandey; Adam P. Bress (Elsevier, 2024)
Objective: Glucagon-like peptide-1 receptor agonists (GLP1-RAs) and sodium-glucose cotransporter 2 inhibitors (SGLT2Is) lower adverse cardiac and kidney events among high-risk patients with diabetes mellitus (DM) and are now guideline-recommended as first-line therapy alongside metformin. However, the adoption of these new treatments from 2015 to 2020 among the highest-risk adults with DM remains unclear. Methods: We performed a cross-sectional analysis of the National Health and Nutrition Examination Surveys (NHANES) 2015-2020 to estimate the use of GLP1-RAs and SGLT2Is among adults with DM overall and by level of cardiovascular and kidney risk (CKR). We defined high CKR by history of atherosclerotic cardiovascular disease (ASCVD), chronic kidney disease (CKD), heart failure, or age ≥55 years with at least 2 ASCVD risk factors (i.e., obesity, hypertension, hyperlipidemia, or current smoker). Results: Overall, 2,432 participants with DM (mean age 60.6 years, 46.8 % female, 58.8 % Non-Hispanic White) were included, of which 1,869 and 563 were with and without high CKR, respectively. Participants with vs. without high CKR were more likely to be older, have higher systolic blood pressure, lower estimated glomerular filtration rate, use oral antidiabetic agents, and have health insurance. Overall, the weighted prevalence of GLP1-RA or SGLT2I was 9.0 % (95 % confidence interval [CI] 6.9-11.0): 4.8 % (95 % CI 3.6-6.1) took GLP1-RAs, and 5.1 % (95 % CI 3.3-7.0) took SGLT2Is. Use of GLP1-RAs or SGLT2Is did not differ between participants with vs. without high CKR (adjusted prevalence ratio [aPR] 1.00; 95 % CI 0.98-1.02). Participants with ASCVD were more likely to be on a GLP1-RA or SGLT2I (aPR 1.28; 95 % CI 1.25-1.31), while adults with CKD were less likely (aPR 0.84; 95 % CI 0.82-0.86). Conclusion: Among US adults with DM, GLP1-RA and SGLT2I use was low regardless of CKR. Data since 2020 analyzing the utilization of GLP1-RAs and SGLT2Is among high-CKR patients with DM is needed to identify implementation strategies for increased utilization.